Low-phosphorus diets during late-finishing decrease cost of gain with minimal effect on growth performance, carcass characteristics, and meat quality - Mavromichalis, I.; Kim, I.H.; Burnham, L.L.; Rantanen, M.M.; Hines, Robert H.; Hancock, Joe D.; Kropf, Donald H.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Partially omitting (up to 66 %) the supplemental inorganic phosphorus (P) source from a late-finishing (190 to 250 lb) diet resulted in slightly greater ADG and backfat thickness, which probably resulted from the greater feed (energy) intake. Meat quality was unaffected by treatment. Thus, during late-finishing, a total P concentration of .40% can be used to decrease diet cost without decreasing performance or meat quality of high-lean pigs.
Keywords: Swine; Phosphorus; Performance; Carcass; Meat